Survey of informal milk retailers in Nairobi, Kenya and prevalence of aflatoxin M1 in marketed milk - Kirino, Y.; Makita, K.; Grace, Delia; Lindahl, Johanna F. (African Journal of Food, Agriculture, Nutrition and Development, 2016)
Aflatoxins are toxic by-products of fungi contaminating maize and other crops; they can be carried over into milk, meat and eggs when livestock eat aflatoxin-contaminated feed or fodder. People who consume such animal products are exposed to the toxins. To assess the aflatoxin contamination status in marketed raw milk and associated risk factors in peri-urban Nairobi, we conducted a census of raw milk retailers in Dagoretti Division, Nairobi, Kenya. Structured questionnaires were filled in by face-to-face interviews with all retailers who agreed to participate in this study. Small portions of milk were purchased from each respondent and tested for aflatoxin M1 (AFM1) using competitive enzymelinked immunosorbent assay (cELISA) tests. Geographic coordinates of each eligible retailer were recorded. A total of 350 milk retailers were visited and 344 were plotted on a map. Of these, 250 retailers answered the questionnaire and a milk sample from each of 200 retailers underwent cELISA analysis for AFM1. Four types of businesses were found: kiosks (71%), dairy shops (21%), street or mobile vendors (3%) and grocery stands (1%); for 4% the business type was not identified. Milk was mainly sourced directly from dairy farms (59%) or from intermediate distributors (35%). Most retailers sold less than 20 litres per day of raw milk. The mean daily milk consumption of the milk retailers’ households was 940 ml for adults and 729 ml for children. Although 58% of retailers had heard about aflatoxins and the majority of them agreed that aflatoxins could be present in milk, only 29% believed that “milk safety cannot be solely judged by sight or taste” and only 6% that “milk is not completely safe even after boiling”. The cELISA test found the mean concentration of AFM1 was 128.7 parts per trillion (ppt) (median=49.9; 95% confidence interval=3.0–822.8) with a maximum of 1675 ppt. Overall, 55% of samples exceeded the European Union maximum level of 50 ppt and 6% exceeded the recommended maximum level of the United States Food and Drug Administration of 500 ppt. Compared to milk from street vendors, a significantly higher amount of AFM1 was detected in milk from kiosks and dairy shops, especially when the milk was sourced from farms without an intermediate distributor. Our findings indicate the need to better understand and manage aflatoxin in milk in Nairobi.